Explosion Pressure Design Criteria For Seals In U.S. Coal Mines - An Update On Work At NIOSH - R. Karl Zipf (The National Institute for Occupational Safety and Health (NIOSH), 2009)
A fatal explosion in a sealed area at the Sago Mine in 2006 prompted researchers and regulators in the United States to re-examine the requirements for explosion-resistant mine seals. Seals are used in underground coal mines to isolate abandoned mining areas from active workings. Prior to the Sago disaster, mining regulations required seals to withstand a 140 kPa explosion pressure. Recent research at the National Institute for Occupational Safety and Health (NIOSH)Pittsburgh Research Laboratory showed that pressures from explosions can far exceed this pressure. U.S. mining regulations now require much stronger seals. Current research focuses on understanding the science, engineering and management of sealed areas of coal mines. Scientific efforts seek understanding of how explosive methane-air mixtures accumulate using measurements and models of the sealed area atmosphere. Additional scientific efforts aim to understand the explosion pressures that can develop using a combination of numerical modeling and experiments. Engineering efforts aim to produce design guidelines for seals that can resist the new higher pressure design criteria. NIOSH researchers are also developing guidance for monitoring of sealed area atmospheres and inertization of potentially explosive gas mixtures within sealed areas. This paper seeks to encourage scientific discussion among international peers since preventing explosions within sealed areas is of interest to underground coal operators and regulators.